2017
DOI: 10.4238/gmr16029648
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW-ARTICLE Intermediate alleles of Huntington’s disease HTT gene in different populations worldwide: a systematic review

Abstract: ABSTRACT. Huntington's disease (HD) is an autosomal dominant progressive neurodegenerative disorder caused by a dynamic mutation due to the expansion of CAG repeats in the HTT gene (4p16.3). The considered normal alleles have less than 27 CAG repeats. Intermediate alleles (IAs) show 27 to 35 CAG repeats and expanded alleles have more than 35 repeats. The IAs apparently have shown a normal phenotype. However, there are some reported associations between individuals that bear an IA and clinical HD signs, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 39 publications
5
21
2
5
Order By: Relevance
“…Hispanic Americans in our study were found to have the highest IA frequency of all evaluated groups (5.6%). In line with these observations, a recent systematic review of global IA prevalence observed that the highest IA frequency in the general population detected to date (8.7%) was found in Brazilians (Apolinario, Paiva, & Agostinho, ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Hispanic Americans in our study were found to have the highest IA frequency of all evaluated groups (5.6%). In line with these observations, a recent systematic review of global IA prevalence observed that the highest IA frequency in the general population detected to date (8.7%) was found in Brazilians (Apolinario, Paiva, & Agostinho, ).…”
Section: Discussionsupporting
confidence: 55%
“…These data suggest that the genetic prevalence rate of HD in admixed populations of Latin America may in fact exceed the prevalence rate in populations of predominant European ancestry. However, only a limited number of studies reporting IA frequencies for Latin America are available (Apolinario et al, ) and recent population‐based prevalence estimates of HD for most of the region are unavailable (Castilhos et al, ; Paradisi, Hernandez, & Arias, ; Rawlins et al, ). The term Hispanic broadly refers to persons of Latin American or Spanish descent, representing a heterogonous group of individuals with varying degrees of admixture from European, African, and Native American ancestry (Bedoya et al, ; Gravel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Huntington hastalığı (HH) otozomal dominant geçişli korenin en sık sebebi olan nörodejeneratif bir hastalıktır [1]. HH'nin kesin tanısı, 4.…”
Section: Introductionunclassified
“…Burada en sık görülen bozukluk depresyondur. Kognitif bozukluk ise özellikle yürütücü fonksiyonlarla ilişkilidir ve seyir sonunda demansa dönüşür [1].…”
Section: Introductionunclassified
“…Huntington hastalığı (HH) otozomal dominant geçişli nörodejeneratif bir hastalıktır 1 .HH ile ilgili genom (IT-15)kromozom 4'ün kısa bacağında (4p16.3 )bulunmaktadır. IT-15 geni huntington proteinini kodlamaktadır.…”
Section: Introductionunclassified